2012
DOI: 10.21608/ajas.2012.267336
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Grain Yield and Some Other Traits in Yellow Maize (Zea mays L.) Inbred Lines

Abstract: Eight advanced inbred lines derived from different yellow maize populations were crossed in a half diallel mating scheme in 2010 season at Gemmeiza Agric. Res. Station. The resultant 28 crosses along with two commercial check hybrids i.e. SC 166 and SC 173 were evaluated at two locations i.e. Gemmeiza and Mallawy Agric. Res. Stations in 2011 season. Mean squares due to crosses, G.C.A. and S.C.A. were highly significant for all studied traits. The ratio of Ʃg2i/ ƩS2ij indicated that the nonadditive gene effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…So, it would not be effective to make selection on the basis of evaluation in a single environment and more environments are needed. Similar results were obtained by El-Hosary (1989), Barakat et al (2003) and Osman et al (2012), They found that the interactions between both types of combining abilities and the environment were highly significant. Variances due to SCA × location were not significant for all studied traits, except for plant height and grain yield per feddan where variances were significant.…”
Section: Analysis Of Variancesupporting
confidence: 87%
“…So, it would not be effective to make selection on the basis of evaluation in a single environment and more environments are needed. Similar results were obtained by El-Hosary (1989), Barakat et al (2003) and Osman et al (2012), They found that the interactions between both types of combining abilities and the environment were highly significant. Variances due to SCA × location were not significant for all studied traits, except for plant height and grain yield per feddan where variances were significant.…”
Section: Analysis Of Variancesupporting
confidence: 87%